2008
DOI: 10.1590/s0103-50532008000400026
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol electrooxidation on Pt-Sn and Pt-Sn-W bulk alloys

Abstract: A oxidação de etanol foi estudada sobre eletrodos Pt-Sn e Pt-Sn-W preparados em forno a arco elétrico. Diferentes técnicas eletroquímicas, tais como voltametria cíclica e cronoamperometria foram utilizadas para avaliar a atividade catalítica desses materiais. O processo de eletro-oxidação também foi investigado in situ por espectroscopia de reflectância na região do infravermelho para determinar intermediários adsorvidos e produtos da reação. Os resultados experimentais indicaram que as ligas Pt-Sn e Pt-Sn-W s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…8 contains the cell performance at 80 C for some representative PtSn/C catalysts prepared here. The open circuit potentials are 0.74 V and 0.72 V for the MW (Metal/NaAc, 1:5) and DPP routes, respectively, indicating good similarity between these methods and other catalysts frequently found in the literature [4,16,24,25]. However, there is a pronounced difference in the power density intensities: the MW catalysts display higher values as compared to the DPP catalyst, namely 37 mW cm À2 against 24 mW cm À2 .…”
Section: Ethanol Electrooxidationsupporting
confidence: 66%
“…8 contains the cell performance at 80 C for some representative PtSn/C catalysts prepared here. The open circuit potentials are 0.74 V and 0.72 V for the MW (Metal/NaAc, 1:5) and DPP routes, respectively, indicating good similarity between these methods and other catalysts frequently found in the literature [4,16,24,25]. However, there is a pronounced difference in the power density intensities: the MW catalysts display higher values as compared to the DPP catalyst, namely 37 mW cm À2 against 24 mW cm À2 .…”
Section: Ethanol Electrooxidationsupporting
confidence: 66%
“…Many attempts have lately been made to optimize and to further improve activity of anode catalysts. One of the most recent concepts involves modification of noble metal nanoparticles with an ultra-thin layer of a tungstates [17][18][19][20][21][22]; consequently, the enhancement of the system's electrocatalytic activity (namely in terms of higher currents recorded, especially those at low potentials, has been observed. An alternate, or complimentary solution, is based on an independent photoelectrochemical oxidation of undesirable intermediate products of ethanol oxidation (such as acetaldehyde and acetic acid) by using especially build for that purpose tandem solar cell [23].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the catalyst, the resins are stoichiometrically mixed with carbon Vulcan XC-72 or any other support, and fired at high temperatures; e.g., 300-400 C. The major advantage of this route is the attainment of robust catalysts with experimental composition close to the nominal one. This method has been employed in the synthesis of a series of Pt-based materials [25,26,30,62].…”
Section: Microemulsion Methodmentioning
confidence: 99%
“…The presence of WO x species assist the electrooxidation of ethanol acting as a Bronstëd acid in the process of dehydrogenation and water molecules dissociation. Ribeiro et al [25] and dos Anjos et al [26] observed a higher catalytic activity for the oxidation of ethanol at PtSnW than at PtSn/C. They attributed the improvement of the catalytic activity to the presence of Sn and W that decreased the overpotential for the intermediate species removal.…”
Section: Bi and Tri-metallic Materials: Effect Of The Co-catalyst On mentioning
confidence: 98%